Alkali-activated materials as coatings deposited on various substrates: A review. (October 2021) - Tian, Qingbo; Wang, Shuo; Sui, Yuwu; Lv, Zhijie
Abstract: Alkali-activated material (AAM) coatings are made from metakaolin, fly ash, granulated blast furnace slag (GBFS), or a mixture of two or more of them as precursor materials. AAM coatings have been deposited on various substrates, such as metals, clay, ordinary Portland cement (OPC)-based mortars or concretes, plywood, glass and ceramic tiles, for fire resistance, anti-corrosive protection, and ionic penetration in aggressive environments. In this paper, the adhesive strength and interfacial boding between coatings and substrates, the coating methods and their characteristics, as well as the application of coatings on various substrates, are reviewed. The appropriate reactions between precursor material and alkaline activator are essential to achieve the strong adhesive strength of coatings on substrates, and to obtain the compatible shrinkage with substrates. The introduction of the additives to precursor materials increases the ability to resist fire, whether by adjusting the expansion of the coating, or by forming intumescent phases. It has been proved that the increased thickness of AAM coatings, largely determined by method of formation, is a significant factor enhancing the fire and corrosion resistance thereof.